InGaAs/GaAsP strain balanced multi-quantum wires grown on misoriented GaAs substrates for high efficiency solar cells - Alonso-Alvarez,D; Thomas,T; Fuehrer,M; Hylton,NP; Ekins-Daukes,NJ; Lackner,D; Philipps,SP; Bett,AW; Sodabanlu,H; Fujii,H; Watanabe,K; Sugiyama,M; et al. (Applied Physics Letters, 2014)
Quantum wires (QWRs) form naturally when growing strain balanced InGaAs/GaAsP multi-quantum wells (MQW) on GaAs [100] 6° misoriented substrates under the usual growth conditions. The presence of wires instead of wells could have several unexpected consequences for the performance of the MQW solar cells, both positive and negative, that need to be assessed to achieve high conversion efficiencies. In this letter, we study QWR properties from the point of view of their performance as solar cells by means of transmission electron microscopy, time resolved photoluminescence and external quantum efficiency (EQE) using polarised light. We find that these QWRs have longer lifetimes than nominally identical QWs grown on exact [100] GaAs substrates, of up to 1 μs, at any level of illumination. We attribute this effect to an asymmetric carrier escape from the nanostructures leading to a strong 1D-photo-charging, keeping electrons confined along the wire and holes in the barriers. In principle, these extended lifetimes could be exploited to enhance carrier collection and reduce dark current losses. Light absorption by these QWRs is 1.6 times weaker than QWs, as revealed by EQE measurements, which emphasises the need for more layers of nanostructures or the use light trapping techniques. Contrary to what we expected, QWR show very low absorption anisotropy, only 3.5%, which was the main drawback a priori of this nanostructure. We attribute this to a reduced lateral confinement inside the wires. These results encourage further study and optimization of QWRs for high efficiency solar cells.